2019
DOI: 10.1186/s12903-019-0802-9
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) regulates the proliferation of human periodontal ligament stem cells and toll-like receptor 4 (TLR4) expression to improve periodontitis

Abstract: Background LncRNA PTCSC3 is a known tumor suppressor, while its roles in other human diseases are unclear. Methods All participants were admitted by The second Affiliated Hospital, School of Medicine, Zhejiang University from January 2016 to January 2018. RT-qPCR, Vectors, cell transfection, In vitro cell proliferation assay and western blot were using to carry out the experiment. Results In this study we found that PTCSC3 was downregulated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Besides protein‐coding genes, differentially expressed lncRNAs have also been identified in periodontitis 16 . Certain differentially expressed lncRNAs have been reported to be critical players in periodontitis 17,18 . In this study, we observed reduced expression levels of DCST1‐AS1 in periodontitis and its enhancing effects on PDLCs’ proliferation, suggesting that DCST1‐AS1 might participate in the pathogenesis of periodontitis through regulating PDLCs proliferation.…”
Section: Discussionsupporting
confidence: 50%
“…Besides protein‐coding genes, differentially expressed lncRNAs have also been identified in periodontitis 16 . Certain differentially expressed lncRNAs have been reported to be critical players in periodontitis 17,18 . In this study, we observed reduced expression levels of DCST1‐AS1 in periodontitis and its enhancing effects on PDLCs’ proliferation, suggesting that DCST1‐AS1 might participate in the pathogenesis of periodontitis through regulating PDLCs proliferation.…”
Section: Discussionsupporting
confidence: 50%
“…Gram-negative bacteria are the major pathogen involved in periodontitis, and their main pathogenic component is the lipopolysaccharide (LPS) that is primarily recognized by TLR4 ( Janssens and Beyaert, 2003 ; Sun et al, 2008 ). A large body of evidence has proven the involvement of TLR4 in periodontitis ( Renn et al, 2018 ; Liu et al, 2019a ). Researchers have revealed that TLR4 can be activated by LPS to regulate NF-κB pathway of PDLSCs to subsequently decrease their osteogenic potential ( Li et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is characterized by an imbalance between proliferation and apoptosis of periodontal ligament cells (PDLCs) 55 . Accumulating evidence has demonstrated that various lncRNAs exert vital roles in the proliferation and apoptosis of periodontitis PDLCs (pPDLCs) 17,56‐63 . Fibroblast growth factor‐2 (FGF2) is a pivotal promoter of PDLSCs proliferation 64 .…”
Section: The Role Of Lncrnas In the Pathophysiology Of Periodontitismentioning
confidence: 99%